Quasi-P-almost class (Q) composition operators - Victor Wanjala (KOMUNITAS Analisis Matematika INDONESIA, 2025)
In this paper, we generalize almost class (Q) operators to Quasi-p-almost class (Q) operators.A bounded linear operator Ξ is said to be a Quasi-p-almost class (Q) operator ifΞ∗2Ξ2(Ξ + Ξ∗) ≥ (Ξ + Ξ∗)(Ξ∗Ξ)2.We characterize this class using the Radon-Nikodym derivativeλ(Ξ2)−1in terms of the multiplicationoperator with respect to λ. Results characterizing this class in terms of weighted composition operatorsare also presented